PENGARUH LATIHAN BENCH PRESS DAN BERAT BADAN TERHADAP HASIL BELAJAR TOLAK PELURU GAYA O'BRIEN SISWA PUTERA KELAS II SMK NEGERI 1 WANAREJA - Sulistiyono, Sulistiyono (Jurnal Pendidikan Jasmani Indonesia, 2011)
<p class="MsoNormal" style="margin-top: 0cm; margin-right: -1.55pt; margin-bottom: .0001pt; margin-left: 0cm; text-align: justify; line-height: 120%; mso-pagination: none; mso-layout-grid-align: none; text-autospace: none;">The aims of this research to investigate: 1) the difference of bench press exercise effect between <p class="MsoNormal" style="margin-top: .15pt; margin-right: -1.4pt; margin-bottom: .0001pt; margin-left: 0cm; text-align: justify; line-height: 121%; mso-pagination: none; mso-layout-grid-align: none; text-autospace: none;">135° and 45° angle, 2) the difference between body weight fat normal and thin normal to the O’Brien style performance, 3) the interaction between the bench press exercise and the body weight to the O’Brien style shot put performance. The research population was 192 male students in 2 grade of SMK Negeri 1 <p class="MsoNormal" style="margin-top: .1pt; margin-right: -1.1pt; margin-bottom: .0001pt; margin-left: 0cm; text-align: justify; line-height: normal; mso-pagination: none; mso-layout-grid-align: none; text-autospace: none;">Wanareja, Cilacap during the academic year 2006/ <p class="MsoNormal" style="margin-top: 2.4pt; margin-right: -1.9pt; margin-bottom: .0001pt; margin-left: 0cm; text-align: justify; line-height: 118%; mso-pagination: none; mso-layout-grid-align: none; text-autospace: none;">2007. There were 40 male student as the samples by using body weight and high test. The result of the research hypothesis test was analysis using two ways Analysis of Variance (ANOVA) with significance degree 95% (á = 0,05), the result i.e.: the first hypothesis test show the value of count is 13,49 higher than the F table á = 0,05 dk (1); (36) as amount of <p class="MsoNormal" style="margin-top: .05pt; margin-right: -1.55pt; margin-bottom: .0001pt; margin-left: 0cm; text-align: justify; line-height: 122%; mso-pagination: none; mso-layout-grid-align: none; text-autospace: none;">4,11 (Fo = 13,49 > Ft = 4,11). The summary: there is different effect between bench press exercise with <p class="MsoNormal" style="margin-top: 0cm; margin-right: -1.3pt; margin-bottom: .0001pt; margin-left: 0cm; text-align: justify; line-height: 11.45pt; mso-line-height-rule: exactly; mso-pagination: none; mso-layout-grid-align: none; text-autospace: none;">135° and 45° angle the result of O’Brien style shot <p class="MsoNormal" style="margin-top: 2.55pt; margin-right: -1.7pt; margin-bottom: .0001pt; margin-left: 0cm; text-align: justify; line-height: 118%; mso-pagination: none; mso-layout-grid-align: none; text-autospace: none;">put. The second hypothesis test show the value of count is 35,95 higher than the F table á = 0,05 dk (1); (36) as amount of 4,11 (Fo = 35,95 > Ft = 4,11). The summary: there is different effect between body weigt fat normal and thin normal the result of O’Brien style shot put. The third hypothesis test show the value of count is 3,83 lower than the F table á = 0,05 dk (1); (36) as amount of 4,11 (Fo = 3,83 < Ft = <p class="MsoNormal" style="margin-top: .35pt; margin-right: -1.35pt; margin-bottom: .0001pt; margin-left: 0cm; text-align: justify; line-height: 122%; mso-pagination: none; mso-layout-grid-align: none; text-autospace: none;">4,11). The summary: there is not interaction between bench press exercise and body weight the result of O’Brien style shot put. <p class="MsoNormal" style="margin-top: .2pt; margin-right: 0cm; margin-bottom: .0001pt; margin-left: 0cm; line-height: 6.0pt; mso-line-height-rule: exactly; mso-pagination: none; mso-layout-grid-align: none; text-autospace: none;"> <p class="MsoNormal" style="margin-top: 0cm; margin-right: -1.4pt; margin-bottom: .0001pt; margin-left: 0cm; text-align: justify; line-height: 128%; mso-pagination: none; mso-layout-grid-align: none; text-autospace: none;">Kata kunci: latihan bench press, berat badan, tolak peluru gaya O’Brien